2019
DOI: 10.3390/nu11071652
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Cardiorespiratory Fitness, and the Metabolic Syndrome

Abstract: Both observational and interventional studies suggest an important role for physical activity and higher fitness in mitigating the metabolic syndrome. Each component of the metabolic syndrome is, to a certain extent, favorably influenced by interventions that include physical activity. Given that the prevalence of the metabolic syndrome and its individual components (particularly obesity and insulin resistance) has increased significantly in recent decades, guidelines from various professional organizations ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
282
2
33

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(328 citation statements)
references
References 110 publications
11
282
2
33
Order By: Relevance
“…77 Beyond that, both resistance training (and resulting improvements in strength and muscle mass) and aerobic exercise are associated with reduced risk of obesity, hypertension, metabolic disease, and survival after critical illness. [78][79][80][81][82] Lifestyle medicine also has significant scope to improve sleep quantity and quality, both of which are associated with immune function and overall mortality. [83][84][85][86] Initiatives such as group consultations and social prescribing can even help to tackle loneliness and social isolation, which are associated with both altered inflammatory processes and increased mortality.…”
mentioning
confidence: 99%
“…77 Beyond that, both resistance training (and resulting improvements in strength and muscle mass) and aerobic exercise are associated with reduced risk of obesity, hypertension, metabolic disease, and survival after critical illness. [78][79][80][81][82] Lifestyle medicine also has significant scope to improve sleep quantity and quality, both of which are associated with immune function and overall mortality. [83][84][85][86] Initiatives such as group consultations and social prescribing can even help to tackle loneliness and social isolation, which are associated with both altered inflammatory processes and increased mortality.…”
mentioning
confidence: 99%
“…Numerous studies have confirmed that physical activity can prevent and reverse the risk factors of metabolic syndrome. Myers, Kokkinos, and Nyelin (2019) noted that a minimum of 150 min of moderate-intensity physical activity per week or 75 min of high-intensity physical activity per week can significantly reduce the risks of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Given the known effect of physical activity on the incidence of chronic disease in adults [9,13], there is a need to assess of metabolic risk markers of chronic disease such as body mass index, blood pressure, blood sugar and level of oxygen saturation in blood, as a part of evaluating health effects of the physical activity intervention [41,42]. These assessments were also included since they were in line with participants need as indicated by them during the initial workshops.…”
Section: Health Testsmentioning
confidence: 99%